2005
DOI: 10.1038/sj.ijir.3901335
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction and HTLV-I infection: a silent problem

Abstract: The human T-lymphotropic virus type I (HTLV-I) is a retrovirus associated with a chronic myelopathy known as HTLV-I-Associated Myelopathy or Tropical Spastic Paraparesis (HAM/TSP). The main objective was to assess the frequency of erectile dysfunction (ED) in HTLV-I-infected individuals from Salvador and other cities from Bahia, Brazil, as well as to verify if sexual dysfunction correlates with urinary symptoms and overall neurological impairment. From January 2001 to April 2004, 218 HTLV-I carriers (111 male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 19 publications
(16 reference statements)
0
23
0
2
Order By: Relevance
“…A tetrahiperreflexia e sinal de Hoffmann positivo são sinais frequentes, apesar do pouco acometimento da força muscular e da sensibilidade dos membros superiores, com resultado compatível com o descrito em publicações anteriores 6,14 . Nota-se a importante prevalência da disfunção erétil nos pacientes masculinos, problema grave que deve ser abordado 30 . Também, existem alterações da função sexual feminina, devido à diminuição da sensibilidade perineal e das próprias limitações físicas, da progressão da doença, entretanto, no presente estudo não foi feita uma análise destes dados por não ser uma pesquisa rotineira neste serviço de reabilitação.…”
Section: Discussionunclassified
“…A tetrahiperreflexia e sinal de Hoffmann positivo são sinais frequentes, apesar do pouco acometimento da força muscular e da sensibilidade dos membros superiores, com resultado compatível com o descrito em publicações anteriores 6,14 . Nota-se a importante prevalência da disfunção erétil nos pacientes masculinos, problema grave que deve ser abordado 30 . Também, existem alterações da função sexual feminina, devido à diminuição da sensibilidade perineal e das próprias limitações físicas, da progressão da doença, entretanto, no presente estudo não foi feita uma análise destes dados por não ser uma pesquisa rotineira neste serviço de reabilitação.…”
Section: Discussionunclassified
“…At each of the 6 visits with complete data (visit 4 was not included), the mean number of work-loss days was greater for HTLV-II participants when compared with that for HTLV-I and HTLV-seronegative participants ( p Ͻ 0.0001 at all visits; figure 2). Using multivariate repeated-measures analysis to control for confounding, HTLV-II participants were shown to report 14…”
Section: Statistical Methods Data Through Visit 7 Conducted In 2004mentioning
confidence: 99%
“…These symptoms and conditions may later progress to HAM or constitute isolated neurologic syndromes associated with HTLV infection. Sensory neuropathy, [6][7][8] gait abnormalities, 9,10 bladder dysfunction, 6,9-12 erectile dysfunction, 13,14 ALS, 15 mild cognitive deficits, 16 and rarely, motor neuropathies 6,8,13,[17][18][19] have all been reported among HTLV-I-infected individuals without HAM. Although less research has focused on HTLV-II, sensory neuropathy has been observed with HTLV-II alone 20 and with HIV coinfection.…”
mentioning
confidence: 99%
“…During the initial phases the most common urinary symptoms are nocturia, urge urinary incontinence and dysuria, progressing to feelings of micturition effort, incomplete bladder emptying and incontinence. 44,45,46 Erectile dysfunction is reported in 88.2% of patients with HAM/TSP, in comparison with a rate of 17% in the general population. 44 Rocha et al 47 observed symptoms suggestive of urinary infection in HTLV carriers, but did not confirm infection by urine culture in the majority of cases (81%).…”
Section: Erectile Dysfunction and Urinary Symptomsmentioning
confidence: 99%